2017
DOI: 10.1039/c7cp02872e
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the evolving microstructure of lithium metal electrodes in 3D using X-ray computed tomography

Abstract: The growth of electrodeposited lithium microstructures on metallic lithium electrodes has prevented their use in rechargeable lithium batteries due to early performance degradation and safety implications. Understanding the evolution of lithium microstructures during battery operation is crucial for the development of an effective and safe rechargeable lithium-metal battery. This study employs both synchrotron and laboratory X-ray computed tomography to investigate the morphological evolution of the surface of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 57 publications
(37 citation statements)
references
References 50 publications
1
36
0
Order By: Relevance
“…It may be possible to use true, evolving Li surfaces, rather than the idealized Li surfaces analyzed here, once data along these lines [38] is available for cells under pressure…”
Section: Propertiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It may be possible to use true, evolving Li surfaces, rather than the idealized Li surfaces analyzed here, once data along these lines [38] is available for cells under pressure…”
Section: Propertiesmentioning
confidence: 99%
“…(The cathode porosity, generally near 30% for commercial cathodes, ensures that its surface is rough.) A significant level of roughness is inevitable on the Li metal as well [11,16,38,39], which can add to the complexity of the stress field.…”
Section: Introductionmentioning
confidence: 99%
“…This porous dead Li layer leads to huge transfer resistance and cell polarization. 55 Before the dendrite-induced short circuit, the impedance of the battery sharply escalates and hence the service life is early terminated.…”
Section: The Significance Of LI Metal Anode In Working Li−s Batteriesmentioning
confidence: 99%
“…It was found that the originally smooth and flat lithium metal surface was crimped by a separator due to the applied pressure during cell assembly. [38] This caused heterogeneous lithium growth and pitting on the surface, highlighting the importance of selecting a proper separator. Researchers were also able to quantitatively track the porosity and pore size of the lithium microstructure during the cycle and concluded that the heterogeneous growth may lead to the formation of the electrically isolated lithium.…”
Section: X-ray Computed Tomography (X-ray Ct)mentioning
confidence: 99%